Identification of key regulatory pathways and genes involved in the dynamic progression of pigmentation in Sinibrama taeniatus - Yuan, Dengyue; Liu, Xiaoqin; Wang, Siya; Wang, Haoyu; Li, Junting; Zhao, Zhe; Wei, Lan; Cheng, Linfeng; Teng, Ran; Wang, Zhijian (Frontiers in Marine Science, 2023)
Intorduction Coloration is a prominent trait in fish that is closely linked to their market value. Fish exhibit a diverse range of body colors, making them an excellent model for studying molecular mechanisms underlying pigmentation. Although regulatory pathways involved in pigmentation have been extensively studied in model fish such as zebrafish and medaka, the presence of varying chromatophore types across different fish species suggests that fish pigmentation mechanisms are not fixed. Therefore, more studies should be conducted on non-model fish. Sinibrama taeniatus is an endemic fish in the upper Yangtze River that is highly valued for its ornamental and edible properties. Methods In this study, we identified three chromatophore types in S. taeniatus and investigated changes in body color, chromatophores, and pigments at different developmental stages. Subsequently, RNA-seq analysis revealed that retinol metabolism, thyroid hormone synthesis, purine metabolism, and pyrimidine metabolism pathway are closely associated with pigmentation. Results Weighted gene co-expression network analysis (WGCNA) identified several hub genes, including mitf, wnt 9a, wnt10b, wnt11, adcy5, edn1, adcy8, and rdh8, that may play an important role in pigmentation. Discussion Overall, our findings provide valuable insights into the role of genes and pathways in fish pigmentation and offer useful information for body color-based molecular breeding programs in aquaculture.